Class A predictions of damage level in an historical fortress induced by twin tunnelling - Boldini, D.; Spaggiari, C.; Abul, J.K.; Fuoco, S.; Lusini, E. (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World, 2023)
Tunnelling below historical city centres requires the accurate analysis of the impact of construction works on cultural heritage monuments, which need to be preserved from any possible damage. In this paper, the undercrossing of an historical masonry structure in the city of Florence (Italy), the Fortezza da Basso, by two tunnels of the new high-speed railway underground line is analysed. The interaction problem is studied by a 3D class-A finite element numerical model. Advanced constitutive laws are adopted to describe the key features of the mechanical behaviour of both soil layers and masonry structures. The results of the analyses show that the excavation process is likely to induce a negligible to slight damage in the historical fortress when a typical surface volume loss of 0.5% is considered in greenfield conditions.